Alcohol use and change over time in firearm safety among families with young children. (1st May 2018) - Martin-Storey, Alexa; Prickett, Kate C.; Crosnoe, Robert
Highlights: Alcohol use is associated with worsened firearms-related outcomes. The majority of families moved to safer firearm practices over time. Higher alcohol consumption reduced the likelihood of moving to safer practices. Firearm safety may be important to address in the context of alcohol use. Abstract: Background: Improperly stored firearms pose a clear health risk to children. Previous research concurrently links alcohol use with lower levels of firearm safety. The objectives of this study were to assess (1) how families move from unsafe to safer firearm storage practices and (2) how parental drinking was associated with moving away from unsafe firearm storage practices. Methods: This study used data from the Early Childhood Longitudinal Study-Birth Cohort, 2003 when children were two years old and again when they were four years old. Parents were asked about firearm storage practices, alcohol consumption, and information to measure other confounding variables. Their responses were used to identify families who engaged in unsafe firearm storage practices ( n = 650) during the initial testing period and to assess how alcohol consumption and other variables were associated with moving to safer firearm storage practices at the second testing period. Results: Families grew more likely to adopt safer firearm storage practices as their children aged, compared with continuing unsafe practices. Multivariate logistic regressions indicated that parental drinking, however, reduced the likelihood that parents moved to safer storage practices, controlling for covariates. Other families- and community-level variables, in particular, family structure, were also associated with the likelihood of moving to safer firearm storage behaviors. Conclusions: Families with higher levels of alcohol use may need additional assistance in addressing firearm safety. The findings call for future research to better understand how physicians can counsel at-risk families to help them store firearms more securely.